The great impacts Houdini. Issue 1 (2nd January 2019) - Briggle, Adam
ABSTRACT: I argue that the broader impacts conversation in research evaluation is designed to look like it addresses difficult questions about progress and the good life, whereas in fact it avoids them. In so doing, this discourse does not stay neutral on these questions. Rather, it supplies a default, unexamined answer. The use of normative anchors, or principles, in talk about Responsible Research and Innovation is laudable but inadequate. The problem is, though, that any adequate conversation would seem hopelessly antiquated if not hostile to the assumed goodness of technoscience.